Neophytadiene from Turbinaria ornata Suppresses LPS-Induced Inflammatory Response in RAW 264.7 Macrophages and Sprague Dawley Rats - Bhardwaj, Meenakshi; Sali, Veeresh Kumar; Mani, Sugumar; Vasanthi, Hannah R. (Inflammation, 2020)
This study investigates the mode of action of Neophytadiene (MT), a molecule isolated from a marine algae Turbinaria ornata in LPS-induced inflammation in both in vitro and in vivo conditions. Neophytadiene (25, 50, 100 μM/mL) was treated to LPS-stimulated RAW 264.7 macrophages cells to identify its anti-inflammatory potential by measuring the level of tumour necrosis factor (TNF-α) by enzyme-linked immunosorbent assay (ELISA) and nitric oxide (NO) using Griess reagent. The mRNA levels of inflammatory cytokines, interleukin (IL-6 and IL-10), and the protein expression of nuclear factor-κB (NF-κB) and inducible nitric oxide synthase (iNOS) were quantified by Western blot analysis. Subsequently, Neophytadiene (12, 25, 50 mg/kg b.wt/p.o) was pre-treated for 7 days to the experimental animals followed by LPS (10 mg/kg) injection interaperitonially. After LPS induction, blood was collected and the haematological parameters were analysed followed by isolation of heart tissue for biochemical molecular and histopathological analysis Neophytadiene significantly inhibited the NO production and inflammatory cytokines TNF-α, IL-6 and IL-10 both in in vitro and in vivo conditions. Further, the expression of TNF-α, IL1β, NF-κB, iNOS, PI3k/Akt and MAPK in the heart tissue was modulated by Neophytadiene significantly confirming the anti-inflammatory potential. Thus, the effect of Neophytadiene on LPS-induced cardiac injury can be attributed to its anti-inflammatory antioxidant and cardioprotective properties.